2017
DOI: 10.1111/nmo.13090
|View full text |Cite
|
Sign up to set email alerts
|

A magnetic resonance imaging study of gastric motor function in patients with dyspepsia associated with Ehlers‐Danlos Syndrome‐Hypermobility Type: A feasibility study

Abstract: This study demonstrates the feasibility of a water challenge MRI protocol to evaluate gastric physiology in the clinical setting. Motility differences between EDS-HT and controls are worthy of further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 38 publications
1
40
0
Order By: Relevance
“…In as little time as 10 minutes we measured significant response which concurred with the findings by Khalaf et al who performed a similar MRI experiment over 270 minutes and found a maximum motility response immediately after ingestion of a test meal . Patients with gastrointestinal motility and functional bowel disorders frequently experience symptoms after ingestion of food and a food provocation test might enable us to explore this reaction further in a range of conditions and diseases . In the case of treatment, response testing could be useful as monitoring tool or inclusion/exclusion criteria to improve the homogeneity of the cohort of interest.…”
Section: Resultssupporting
confidence: 87%
“…In as little time as 10 minutes we measured significant response which concurred with the findings by Khalaf et al who performed a similar MRI experiment over 270 minutes and found a maximum motility response immediately after ingestion of a test meal . Patients with gastrointestinal motility and functional bowel disorders frequently experience symptoms after ingestion of food and a food provocation test might enable us to explore this reaction further in a range of conditions and diseases . In the case of treatment, response testing could be useful as monitoring tool or inclusion/exclusion criteria to improve the homogeneity of the cohort of interest.…”
Section: Resultssupporting
confidence: 87%
“…In their paper Khalaf and co‐workers set normal limits for gallbladder and gastric volumes, small bowel motility and water content, whole gut transit, GI peptides and symptom data when using this test meal. Others have described an under 60 minutes MRI protocol to examine gastric motility, accommodation and emptying together with the duodenal response following a simple water stimulus . We have used a practical 30‐minutes stimulation test for small bowel motility assessment, demonstrating a significant response to a caloric challenge in fasted healthy subjects within a time frame of less than 10 minutes …”
Section: Study Protocolsmentioning
confidence: 99%
“…A study in Ehlers‐Danlos syndrome‐Hypermobility type patients and controls showed that the increase in gastric motility following a water challenge was significantly lower in Ehlers‐Danlos syndrome‐Hypermobility type patients with functional dyspepsia compared to controls …”
Section: Clinical Implementationmentioning
confidence: 99%
See 2 more Smart Citations